Evaluation of Tear Strength of Two Types of Iralgin and its Comparison with Similar Alginate Impression Material - Fayaz, Amir; Noori, Abolghasem (Journal of Dental School, 2019)
Objectives: Among the various impression materials, for alginate tear strength is probably more important than the compressive strength. The tear strength is important when an impression involves a mechanical undercut and/or lacks bulk strength to resist tearing. This study evaluated tear strength of Iralgin and compared it with tear strength of Alginoplast. Methods: In this invitro experimental study A mold was made with 100mm×20mm×1mm dimensions and a longitudinal prominence in 0.3 mm depth. Twenty–seven specimens (9 Super Iralgin, 9 Pocket Iralgin, and 9 Alginoplast) were selected non–randomizedly. Each specimen prepared corresponding to manufacturer and injected into the mold. And the mold was placed under press. After removing the mold from press, every specimen formed as a trouser-shaped specimen. The specimen was pulled in tensile machine with 50 mm/min speed. The data of specimens in different groups were statistically analyzed using one-way ANOVA, Kolmogorov-Smirnov, and Levene’s tests. Results: Mean of tear strength in first specimen (Super Iralgin), second specimen (Pocket Iralgin), and third specimen (Alginoplast) were 640±38 grf/cm², 500 ±20grf/cm², and 1100±27 grf/cm² respectively. According to ANOVA test, the mean of tear strength was not equal in three specimens (p<0.01). According to LSD Multiple Comparison, the first and second specimens were same in tear strength, whereas the third specimen was different from the two former (p<0.05 and p<0.01). Conclusion: Super Iralgin and pocket Iralgin were the same in tear strength. Alginoplast was significantly higher than super and pocket Iralgin in tear strength.